One-Pot Synthesis of CeO2 Modified SBA-15 With No Pore Clogging for NO Reduction by CO - Ma, Kaili; Zhang, Hongliang; Tang, Changjin; Dong, Lin (Frontiers in Environmental Chemistry, 2021)
CeO2 modified SBA-15 composites have been prepared by adding cerium precursor (Ce(NO3)3·6H2O) directly into the mixture of soft template (P123), silica precursor (TEOS) and urea aqueous solution but without mineral acid. The products were characterized by X-ray fluorescence (XRF), powder X-ray diffraction (XRD), N2 physisorption and transmission electron microscopy (TEM). Results indicated that ceria were successfully grafted onto mesoporous silica matrix and no pore clogging was observed. Both ceria content and mesoporous ordering of the final products were found to depend on urea amount. Compared to CeO2/SBA-15 from conventional impregnation method, the one-pot synthesis not only showed simple and green operation, but also superior catalytic performance in NO+CO reaction after loaded with CuO. It was revealed that both the presence and location of ceria had great influence on the reducibility of CuO, and the catalytic performances were intimately related to the redox properties of crystalline CuO. That is, higher NO conversion and N2 selectivity were achieved over catalyst with easier reduction of crystalline CuO.